Science at high-altitude sites of ARIES - Astrophysics and atmospheric sciences - Sagar R.; Naja M.; Maheswar G.; Srivastava A.K. (My University, 2025)
In this article we discuss various frontline research activities those are being carried out in the fields of Astronomy and Astrophysics and Atmospheric Sciences at Aryabhatta Research Institute of Observational Sciences (ARIES) using the existing and upcoming observational facilities at two high latitude sites - Manora Peak and Devasthal. Both sites are located at Devabhumi of Nainital District, Uttarakhand in the central Himalayas. The important results obtained from these research activities are highlighted and upcoming international observational facilities in the institute are discussed.